Special aspects of geriatric patients with sepsis presenting to emergency services [Besonderheiten beim geriatrischen Patienten mit Sepsis im Notfalldienst] - Heppner, Hans Jürgen (Notfall und Rettungsmedizin, 2019)
The demographic shift leads to an increasing number of elderly being treated by emergency services (ES). In this growing collective of elderly patients, sepsis is an important determinant in adverse outcome and thus adapted strategies in preclinical services to adjust diagnostics and treatment are required. Because infections are a common reason to call ES and are also responsible for many deaths among the elderly, sepsis is becoming a major health care problem in the aging society. The geriatric patient is defined by multimorbidity, functional decline and loss of autonomy. Sepsis as a systematic inflammatory response to bacterial infection is still associated with high mortality. Therefore, early detection and initiating of therapeutic bundles is crucial to improve outcomes. Diagnostic strategies and adapted screening and assessment tools must be implemented. Educational programs for physicians and paramedics are as essential as standardized operating procedures for sepsis. Knowledge of the specific characteristics and symptoms of serious infections in the elderly and further research are necessary to be able to ensure the best care for this fragile population.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Bacterial infection; Elderly; Emergency care; Emergency medical services; Geriatrics